2019
DOI: 10.1021/acs.jpcc.8b12549
|View full text |Cite
|
Sign up to set email alerts
|

Phenylated Acene Derivatives as Candidates for Intermolecular Singlet Fission

Abstract: Singlet fission (SF), a spin-conserving process where one singlet exciton is converted into two triplet excitons, may improve the efficiency of organic photovoltaics. Only a few materials have been experimentally observed to undergo intermolecular SF, most of which are acenes and their derivatives. Using many-body perturbation theory in the GW approximation and the Bethe−Salpeter equation, we systematically investigate the electronic and excitonic properties of tetracene, pentacene, and their phenylated deriva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
60
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(64 citation statements)
references
References 89 publications
3
60
0
Order By: Relevance
“…The SHB packing motif is characterized by strong intermolecular electronic coupling within a dimer, but weak coupling between dimers. This typically results in smaller band dispersion than in HB crystals, in which there is strong electronic coupling between π‐stacked molecules, as previously shown for the two polymorphs of perylene [60] . The band structure of terrylene, shown in the SI, exhibits modest band dispersion, similar to quaterrylene and SHB perylene [60] …”
Section: Resultsmentioning
confidence: 52%
See 2 more Smart Citations
“…The SHB packing motif is characterized by strong intermolecular electronic coupling within a dimer, but weak coupling between dimers. This typically results in smaller band dispersion than in HB crystals, in which there is strong electronic coupling between π‐stacked molecules, as previously shown for the two polymorphs of perylene [60] . The band structure of terrylene, shown in the SI, exhibits modest band dispersion, similar to quaterrylene and SHB perylene [60] …”
Section: Resultsmentioning
confidence: 52%
“…The exciton wave functions were converged using a supercell of 4×10×4 based on the criterion proposed by Liu et al [82] . The degree of singlet exciton charge transfer character (%CT) was calculated by double‐Bader analysis (DBA) [60,82] . The results for rubrene and pentacene are from Wang et al., [83] the results for quaterrylene, perylene, and tetracene are from Wang et al., [60] and the results for anthracene are from Liu et al [82] …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Structural considerations and dilution of acene molecules on the inter-triplet interactions have been considered, but the measurements could not distinguish between herringbone or slip-stacked . 22,31 Several theoretical studies compare molecular systems with stacked or herringbone motifs in their crystal packing, addressing the effect of the relative orientation between neighbouring chromophores on the spin and thermodynamics of SF and subsequent exciton migration, [32][33][34][35] but to our knowledge no such study has been reported experimentally in solid-state crystalline systems.…”
mentioning
confidence: 99%
“…Calculations have predicted that the optimal geometry for SF is that which results in a substantial orbital overlap for both HOMO and LUMO, however this has been attributed to both herringbone and slip-stacked configurations. 12,30,[32][33][34][35] Therefore, a combined experimental and theoretical methodology that allows to isolate and distinguish the kinetics of herringbone and slip-stacked dimers in the SF process would be a valuable addition to the field.…”
mentioning
confidence: 99%